Pengalaman Hidup Ibu PKK Perumahan BPI Semarang dalam Menerapkan Nilai Humanistik di Lingkungan Komunitas : Pendekatan Fenomenologi - Selfi Ana Andriyanti; Ahmad Aitdullah; Salsabila Fithri Zatin; Nasya Akmala; Dewi Asyikhah; Siti Hikmah Anas (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
This study aims to understand how PKK mothers in BPI Semarang give meaning to their life experiences in building humanistic values ​​within the community. Using a qualitative phenomenological approach, data were obtained through in-depth interviews, observations, and documentation studies. Data analysis was conducted by identifying themes of experience formulated based on Carl Rogers' humanistic theory, including empathy, unconditional acceptance, openness, and self-actualization. The results indicate that the PKK serves as a space that facilitates members' mutual support, mentoring, and development of their potential, allowing humanistic values ​​to naturally emerge in community interactions.